2018
DOI: 10.20524/aog.2018.0263
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic gastrointestinal disorder: is it what it seems to be?

Abstract: Background:Eosinophilic gastroenteropathy is an uncommon condition whose causes can be numerous and non-specific. The aim of the study was to characterize the presence of gastrointestinal disorders in the adult Maltese population and assess the degree of association with atopic diseases.Methods:Adult patients with gastrointestinal eosinophilia in the gastrointestinal tract on histology were identified and their clinical case notes were reviewed. Patients were interviewed and asked questions regarding asthma, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
3
0
2
Order By: Relevance
“…Aunque el pronóstico ha sido reportado como favorable, la progresión de la enfermedad con períodos alternantes de actividad inflamatoria y remisión han sido descritos 19 . Casos graves de hemorragia digestiva masiva, estenosis, vólvulo, invaginación y perforación han sido reportados [20][21][22][23] . Autores han mostrado que la CEo sería más agresiva en adolescentes y adultos, mientras que en la población pediátrica sería más leve resolviéndose a los días de realizar una restricción de los alimentos gatillantes 19 .…”
Section: Cuadro Clínicounclassified
See 1 more Smart Citation
“…Aunque el pronóstico ha sido reportado como favorable, la progresión de la enfermedad con períodos alternantes de actividad inflamatoria y remisión han sido descritos 19 . Casos graves de hemorragia digestiva masiva, estenosis, vólvulo, invaginación y perforación han sido reportados [20][21][22][23] . Autores han mostrado que la CEo sería más agresiva en adolescentes y adultos, mientras que en la población pediátrica sería más leve resolviéndose a los días de realizar una restricción de los alimentos gatillantes 19 .…”
Section: Cuadro Clínicounclassified
“…Por otra parte, la presencia de eosinofilia colónica no debe ser considerada un elemento exclusivo de la CEo. Estudios retrospectivos han mostrado que hasta un 25% de los pacientes inicialmente catalogados como CEo pueden desarrollar finalmente una enfermedad de Crohn o una colitis ulcerosa 11,20 . Ciertos criterios o hallazgos histológicos pueden apoyar el diagnóstico de CEo, destacando una menor intensidad del infiltrado inflamatorio, aumento en la degranulación de los mastocitos, presencia de depósitos de fibrina y un aumento de la IgE en áreas perineurales de la mucosa 43 .…”
Section: Anatomía Patológicaunclassified
“…To date, several studies have demonstrated the importance of eosinophil (Eo) infiltrating the intestinal mucosa and lamina propria. 59 , 60 …”
Section: Invasive Examsmentioning
confidence: 99%
“…This is revealed by a recent study reporting that patients with eosinophil-predominant inflammation have a lower risk of disease flares and hospitalization than those with a neutrophil-predominant inflammation [ 87 ]. It is worth noting that an increased number of eosinophils is a hallmark not only of IBD but also of a different disease, known as eosinophilic colitis (EC) [ 88 ]. This disorder is erroneously diagnosed as IBD in around 25% of the patients with EC.…”
Section: Type 2 Associated Immune Cells In Ibdmentioning
confidence: 99%